PEMANFAATAN LAHAN PEKARANGAN UNTUK PENINGKATAN PENDAPATAN RUMAH TANGGA MELALUI BUDIDAYA IKAN LELE SISTEM BIOFLOK - Suryadi; Zuriani; Martina; Murdani (Global Science Society, 2021)
The increasingly massive corona outbreak has disrupted the process of fulfilling people's needs because their incomes are falling significantly. To deal with these problems, the community must be able to create a business in order to earn income so as to maintain the survival of their families. The environmental condition of the yard where the villagers live is generally relatively spacious. Many of the yard's land is not used or left empty. Another potential that people in this region have is the availability of water that is quite abundant. Catfish cultivation activities in the yard can be one of the alternatives in increasing household income, especially during this pandemic situation. Market demand for catfish is relatively high, so catfish farming business can be the right choice to start a business in order to increase the income of gampong cot girek community. Cultivation of catfish in a pond tarpaulin with bioflok technology system produces high productivity and efficiency and environmentally friendly.